The Influence of Tax Relaxation, Tax Sanctions, and Income Levels on Compliance With the Rural and Urban Land and Building Tax in Palu City - DIN, Muhammad; SALSABILA, Meita Gania; JURANA, Jurana; TANRA, Andi Ainil Mufidah (Journal of Governance, Taxation and Auditing, 2024)
This study aims to evaluate the extent to which tax relaxation, the imposition of sanctions, and income levels influence taxpayer compliance in fulfilling their obligation to pay the Rural and Urban Land and Building Tax in Palu City. A quantitative approach with a survey method was employed, using primary data collected through questionnaires distributed to registered taxpayers. Multiple linear regression analysis was used to examine the relationships between the studied variables. The findings indicate that all three independent variables positively influence taxpayer compliance, with income level being the most dominant factor, followed by tax sanctions and tax relaxation. These results highlight that individuals’ economic capacity plays a key role in determining compliance, while sanctions and relaxation function as supporting tools to encourage tax-abiding behavior. Based on these results, it is recommended that local governments strengthen tax collection strategies based on taxpayers' financial capacity, while maintaining firm and fair sanction enforcement policies. Tax relaxation should be applied selectively to ensure it provides benefits without diminishing public tax awareness.